PROGRAM PENGEMBANGAN SUMBER DAYA MANUSIA PESANTREN NURUL IMAN SEBAPO MUARO JAMBI - Shalikhah, Khalifatul Maratus; Malik, Abd; Fridiyanto, Fridiyanto; Sodiah, Sodiah (Jurnal Manajemen Pendidikan, 2025)
The importance of the position of Human Resources (HR) in Islamic boarding schools as the subject and object of knowledge transfer between kyai, ustad and students, requires improvement in quantity and quality. This study found a HR improvement program at the Nurul Iman Sebapo Muaro Jambi Islamic Boarding School, which was studied through a qualitative approach with in-depth observation and structured interviews. The HR development program of the Nurul Iman Sebapo Islamic Boarding School runs in a structured and comprehensive manner, such as massive promotion both in study groups and social media, analyzing HR needs, providing training to improve the abilities of students, and involving the community in Islamic boarding school activities. The improvement of teaching HR is carried out through training activities, increasing literature support, and policies on the use of facilities. The superior student programs of the Islamic boarding school are memorizing the Al-Qur'an, the weton and sorogan learning methods, and uniting the salaf and kholaf Islamic boarding school systems. The Islamic boarding school provides literature support that can be used by students and teachers.